Kelimpahan dan Fluktuasi Populasi Artropoda Tanaman Padi (Oryza sativa L.) Pada Lahan Sawah Di Kecamatan Cakung, Jakarta Timur - Alwi, Fauzan; Afifah, Lutfi; Adhi, Satriyo Restu; Koswanudin, Dodin (Agriculture Faculty of Flores University, 2024)
The status of arthropod diversity and biodiversity in Jakarta is often ignored, so the development of Plant Disturbing Organisms (Pests) is increasing. This has spurred farmers managing rice fields (Oryza sativa L.) to carry out unwise pest control on the remaining 414 hectares of land. The purpose of this study was to determine how the percentage of arthropod abundance based on order and fluctuations in arthropod populations on several rice fields in Cakung District, East Jakarta, and as information material in pest control based on Integrated Pest Management (IPM) that is appropriate in the field. The method used in this research is non-experimental with a direct survey method in the rice fields of the Maju Bersama (MB), Ujung Menteng (UM), dan Sawah Abadi (SA) in the vegetative planting phase until the harvest of rice plants. From the findings, the highest percentage of arthropod abundance was found in the order Diptera (36.73%), Araneae (19.45%), Hymenoptera (14.20%), Hemiptera (14.03%), Coleoptera (9, 32%), Lepidoptera (4.75%), Odonata (0.73%), Orthoptera (0.57%), Thysanoptera (0.07%), Heteroptera (0.05%), Dermaptera (0.05%), Isoptera (0.03%), and Psocodea (0.02%). Fluctuations in arthropod populations during one growing season increased starting from 6 - 8 MST, this is thought to be due to the use of various types of synthetic and sustainable pesticides that can affect the diversity of arthropods in rice fields. Therefore, it is necessary to conduct further research on the resistance level of pest arthropods to synthetic pesticides in rice fields.